(untitled) (Jurnal Teknologi (Sciences & Engineering), 2017)
Basic principles of transportation are safety and security, efficiency and equity. The traffic accident rate in Indonesia is still considerably high. In 2014 as reported by the national police, with around 263 accidents per day. Of reported casualties per day, 77.5 people are fatalities, 73.5 people are serious injuries, and 301 people are slightly injuries. Total of the Property Damage Only (PDO) is IDR250,110,380,000 (US18.547 million). To estimate the economic impacts of accidents, the number of accident casualties and accident costs are the most needed data. The aims of this study is to analysis traffic accidents cost using Human Capital Method. The research location in Purbalingga, Central Java, Indonesia using data from 2010-2015. The accident cost analysis based on the casualty severity of accidents is fatal, seriously injured, slightly injured, and PDO. Components of accident costs include costs to repair vehicle, administrative cost, medical care, and potential loss of human productivity, and human cost. Casualty accident costs by severity type: fatality is IDR501,210,320 (US37,168), serious injury is IDR18,874,950 (US1,400), slight injury is IDR6,255,708 (US464), and property damage only is IDR3,047,914 (US226). Total accident cost in Purbalingga was estimated IDR236,517,103,652 (US17,539,274) or 1.27% of the gross domestic product.Â Â